Christian sermons and the law of defamation in Cameroon: A common Law approach (TEST Trento Student Law Review, 2022)
The statutory guarantee of the right to worship and practice any religion in Cameroon entails the freedom to make utterances within Christian sermons and an obligation not to attack the reputation of individuals. Christian sermons have served as a medium for defamation, especially with revivalist or Pentecostal churches as they are commonly known. These institutions establish strong links with their worshipers causing them not to see any defects in their practices even if an injury to their reputation might lead to ostracism. Thus, persons whose reputations are injured hardly lay claims, as they fear being termed evil. This paper has been accomplished through visits to some churches, informal interviews, analysis of legal instruments, and content analysis of relevant literature. It establishes that even though Christian sermons have an impact on building good morals, they may also take advantage of the obedience of worshipers, ruining the lives of some individuals by injuring their reputations through false statements in sermons. This paper, therefore, demonstrates the possibility of laying claims for defamation in Christian sermons and proposes that massive sensitization on the existence of civil and criminal liabilities for defamation should be done to create awareness among aggrieved persons and to reduce the negative effect of fanaticism
Keywords: Christian; Sermons; Defamation; Common law; Cameroon